From traditionally to democratic management in the scope of Education (Research, Society and Development, 2022)
The present work is the result of a qualitative bibliographic research that aimed to understand the concepts of traditional educational management and democratic management and to analyze the transformations that occurred from the first to the second, as well as in the role of the director for the manager. For data collection, some articles, documents and books on the subject were selected, readings, records and moments of group study were carried out for the writing of the article in vogue. Data analysis followed Laurence Bardin's content analysis. As a result, it is evident that the act of managing was previously synonymous with centralization, authoritarianism and punishment. Currently, due to new possibilities in the world, a different way of managing is born, some of the characteristics of this new management are decentralization, participation and democracy. Democratic management is defended by law and must be included in all public schools in Brazil. It is concluded from the research that democratic management is active participation among the various subjects involved in the school environment, it is freedom in the elaboration and acceptance of the pedagogical political project, on the other hand, traditional school management gives power to the director to make decisions, without the active participation of other education professionals.